Maintaining genetic integrity with high promiscuity: Frequent hybridization with low introgression in multiple hybrid zones of Melocactus (Cactaceae) - Khan, Gulzar; Franco, Fernando F.; Silva, Gislaine A.R.; Bombonato, Juliana R.; Machado, Marlon; Alonso, Diego P. [UNESP]; Ribolla, Paulo E.M. [UNESP]; Albach, Dirk C.; Moraes, Evandro M. (My University, 2020)
Hybridization and introgression between species in contact/hybrid zones provide important insight into the genetic and ecological mechanisms of speciation. Cactaceae represents the most important radiation of true succulent angiosperms in the New World. This diversification continues to date, with species experiencing few intrinsic barriers to gene flow and the frequent occurrence of natural hybridization. Here, we used RAD-Seq single-nucleotide polymorphism (SNP) data to investigate the genetic architecture of hybridization in four hybrid zones hosting Melocactus concinnus and four congeneric species (M. ernestii, M. glaucescens, M. paucispinus, and M. zehntneri). Our results revealed that M. concinnus is highly promiscuous in sympatric areas and hybridizes with various species distributed in Morro do Chapéu (Diamantina Plateau, Bahia), eastern Brazil. However, the contemporary genomic introgression among the investigated species is very low (c. 2–5%), confirming that even in the face of hybridization, Melocactus species maintain their genetic integrity. The genomic cline approach showed a large fraction of loci deviating from a model of neutral introgression, where most of the loci are consistent with selection favoring parental genotypes. Our results suggest the occurrence of weak premating but strong postmating reproductive isolation in the analyzed cactus species. Furthermore, as most of the Melocactus species are restricted in distribution, hybridization might negatively affect their integrity if hybrids replace the parental species.
Keywords: Cactaceae; ddRAD-Seq; Diamantina Plateau; Hybridization; Interspecific gene flow; Xeric enclaves